2020
DOI: 10.1021/acs.chemmater.9b04066
|View full text |Cite
|
Sign up to set email alerts
|

Layered Cathode Materials for Lithium-Ion Batteries: Review of Computational Studies on LiNi1–xyCoxMnyO2 and LiNi1–xyCoxAlyO2

Abstract: At present the most successful rechargeable battery is the Li-ion battery, due to the small size, high energy density, and low reduction potential of Li. Computational materials science has become an increasingly important tool to study these batteries, and in particular cathode properties. In silico studies of cathode materials have proven to be a valuable tool to understand the workings of cathodes, without having to do sophisticated experiments. First-principles and empirical computations have been used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(119 citation statements)
references
References 392 publications
3
115
0
1
Order By: Relevance
“…This may allow for the oxide to maintain generally unchanged structural parameters, creating a metastable configuration. This can be, to some degree, related to the peculiar structural differences observed between the electrochemically and chemically lithiated (i.e., intercalated with Li) layered oxide samples at room temperature [36][37][38].…”
Section: Crystal Structurementioning
confidence: 99%
“…This may allow for the oxide to maintain generally unchanged structural parameters, creating a metastable configuration. This can be, to some degree, related to the peculiar structural differences observed between the electrochemically and chemically lithiated (i.e., intercalated with Li) layered oxide samples at room temperature [36][37][38].…”
Section: Crystal Structurementioning
confidence: 99%
“…Among these power sources, advanced lithium ion batteries (LIBs) are the most appropriate ones for electrochemical propulsion, since they may provide the necessary high energy density, cycle life, stability, and reasonable safety [1][2][3][4][5][6][7][8][9][10][11]. The limiting factor of energy content in LIBs are the positive electrodes (cathodes) and their improvement is much more effective compared to other parts of batteries to get high energy density [12].…”
Section: Introductionmentioning
confidence: 99%
“…The dopants' effects on the cathode materials are influenced by several important properties, including ionic charge, ionic size, and magnetism. [21] These effects help to explain the mechanisms through which these dopants at low concentration affect the behavior of NCM cathode materials (see later in the Results and Discussion Section).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have concluded that different dopants have distinct effects on the cathode materials, such as suppressing Li/Ni cation mixing, “pillar effect”, and impeding the intergranular cracks. The dopants’ effects on the cathode materials are influenced by several important properties, including ionic charge, ionic size, and magnetism [21] . These effects help to explain the mechanisms through which these dopants at low concentration affect the behavior of NCM cathode materials (see later in the Results and Discussion Section).…”
Section: Introductionmentioning
confidence: 99%